Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Help needed here please help

Help Needed Here Please Help class=

Sagot :

Answer:

g(f(x))= (x+3)(x+3)

Step-by-step explanation:

f(x) =x² + 6x +7

g(x)= x + 2

1st Step: Substitute the x in g(x) =x + 2 by the value of f(x)

g(f(x))= (x² + 6x +7) + 2

g(f(x))= x² + 6x + 9

2nd Step: Simplify

g(f(x))= x² + 6x + 9

g(f(x))= (x+3)(x+3)